Effect of Thawing Methods on Thawing Quality of the Frozen Stripped-Walnut Kernel - Xing LI; Yonglun WANG; Miao YANG; Zina LIN; Huaide XU (Shipin gongye ke-ji, 2023)
To explore the effect of different thawing methods on the quality of frozen stripped-walnut kernel, the walnut kernel was soaked in warm water to remove the inner seed coat and then frozen as the test material. The color value, texture, free amino acids, VE, unsaturated fatty acids, rancidity index, volatile composition and microtissue structure of walnut after air thawing at room temperature, microwave thawing, refrigerator thawing at 4 ℃ and room temperature ultrasound thawing were measured. The results showed that the content of total free amino acids, VE, unsaturated fatty acids of stripped-walnut kernel after microwave thawing was higher, and the aroma of roasting was relatively stronger. However, the walnut kernel darkens, the oil oxidation was serious, and the pores between cells were relatively large. The walnut kernel color was the worst after thawing in air at room temperature, and the degree of oxidation was serious. After thawing at 4 ℃ and ultrasonic thawing at room temperature, walnut kernel brightness was higher, the texture was good, the total amount of free amino acids was significantly (P<0.05) higher than that of other thawing methods, the content of unsaturated fatty acids was higher, slight oxidation of walnut kernel, the homogeneity between the storage cells was much better. In conclusion, 4 ℃ refrigeration thawing and room temperature ultrasound thawing could better reduce the oxidation of oil during thawing, retain color and nutrition of walnut, and ensure the thawing quality of stripped-walnut kernel.